Towards elimination of mother‐to‐child transmission of HIV in Rwanda: a nested case‐control study of risk factors for transmission - Eric Remera; Placidie Mugwaneza; Frédérique Chammartin; Augustin Mulindabigwi; Gentille Musengimana; Jamie I. Forrest; Fabian Mwanyumba; Ng'oma Kondwani; Jeanine U. Condo; David J. Riedel; Edward J. Mills; Sabin Nsanzimana; et al. (BMC, 2021)
Abstract Background Mother-to-child HIV transmission (MTCT) has substantially declined since the scale-up of prevention programs around the world, including Rwanda. To achieve full elimination of MTCT, it is important to understand the risk factors associated with residual HIV transmission, defined as MTCT at the population-level that still occurs despite universal access to PMTCT. Methods We performed a case control study of children born from mothers with HIV with known vital status at 18 months from birth, who were followed in three national cohorts between October and December 2013, 2014, and 2015 in Rwanda. Children with HIV were matched in a ratio of 1:2 with HIV-uninfected children and a conditional logistic regression model was used to investigate risk factors for MTCT. Results In total, 84 children with HIV were identified and matched with 164 non-infected children. The median age of mothers from both groups was 29 years (interquartile range (IQR): 24-33). Of these mothers, 126 (51.4 %) initiated antiretroviral therapy (ART) before their pregnancy on record. In a multivariable regression analysis, initiation of ART in the third trimester (Adjusted Odds Ratio [aOR]: 9.25; 95 % Confidence Interval [95 % CI]: 2.12-40.38) and during labour or post-partum (aOR: 8.87; 95 % CI: 1.92-40.88), compared to initiation of ART before pregnancy, increased the risk of MTCT. Similarly, offspring of single mothers (aOR: 7.15; 95 % CI: 1.15-44.21), and absence of postpartum neonatal ART prophylaxis (aOR: 7.26; 95 % CI: 1.66-31.59) were factors significantly associated with MTCT. Conclusions Late ART initiation for PMTCT and lack of postpartum infant prophylaxis are still the most important risk factors to explain MTCT in the era of universal access. Improved early attendance at antenatal care, early ART initiation, and enhancing the continuum of care especially for single mothers is crucial for MTCT elimination in Rwanda.